Clinical Laboratory Tests in Some Acute Exogenous Poisonings - Tufkova Stoilka G.; Yankov Ivan V.; Paskaleva Diana A. (Folia Medica, 2017)
Background: There is no specific toxicological screening of clinical laboratory parameters in clinical toxicology when it comes to acute exogenous poisoning.